Hijab and Mountaineering: A Semiotic Study of Piety, Agency, and Resistance in the Pendaki Hijabers Community, Indonesia - Mukhlishin, Ahmad; Mushodiq, Muhamad Agus; Maba, Aprezo Pardodi (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2025)
This study aims to analyze the layered meanings of the hijab within the Pendaki Hijabers community in Indonesia. The research seeks to explain how the hijab functions not only as a religious obligation but also as a cultural signifier of piety, agency, and resistance, making it important to understand its role in shaping Muslim women’s identity in unconventional public spaces. Using a qualitative approach, the study employed in-depth interviews, participant observations during mountain expeditions, and documentation of community campaigns. The data were analyzed through Roland Barthes’ theory of cultural semiotics to identify the denotative, connotative, and mythological meanings of the hijab. The results reveal three key layers of meaning. At the denotative level, the hijab serves as a sign of obedience and piety. At the connotative level, it becomes a symbol of freedom and inclusivity, challenging stereotypes of restriction. At the mythological level, the hijab embodies resistance and social transformation through activities such as daʿwah, the GEMAR (Gerakan Menutup Aurat) campaign, and community service. These findings contribute to religious and cultural studies by offering new insights into the relationship between faith, gender, and physical endurance. They also suggest practical implications for gender equality advocacy, daʿwah strategies, and the promotion of inclusive public spaces for women. The originality of this research lies in situating the hijab within the context of extreme outdoor activities—a domain rarely addressed in previous studies—and in demonstrating how religious symbols operate as dynamic cultural signifiers that bridge devotion, empowerment, and ideological resistance.